2017
DOI: 10.4103/0366-6999.211536
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidences for the Use of UEscope in Airway Management

Abstract: Objective:UEscope is a new angulated videolaryngoscope (VL). This review aimed to describe the features of UEscope and provide clinical evidences regarding the efficacy and safety of this video device in adult tracheal intubation and its roles in airway management teaching.Data Sources:The Wan Fang Data, CNKI, PubMed, Embase, Cochrane Library, and Google Scholar were searched for relevant English and Chinese articles published up to January 15, 2017, using the following keywords: “HC video laryngoscope”, “UE v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 29 publications
0
26
1
Order By: Relevance
“…The UEScope consistently provided better laryngeal view, a shorter time to laryngeal visualization and intubation compared to direct laryngoscopy. [ 19 ] In contrast to these results in real-life patients our manikin study showed comparable results in overall intubation success and time to glottis visualization and intubation in airway scenario A.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The UEScope consistently provided better laryngeal view, a shorter time to laryngeal visualization and intubation compared to direct laryngoscopy. [ 19 ] In contrast to these results in real-life patients our manikin study showed comparable results in overall intubation success and time to glottis visualization and intubation in airway scenario A.…”
Section: Discussioncontrasting
confidence: 67%
“…A recent review reported that the UEScope may provide more benefits than other video laryngoscopes in patients with normal and difficult airways. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Many different videolaryngoscopes for pediatric patients are available, but not all can be used in all age groups [23, 30]. UEScope is a portable videolaryngoscope [29] invented in 2010, equipped with several blades for different age groups. Its specific feature is the angulated blade [29].…”
Section: Introductionmentioning
confidence: 99%
“…UEScope is a portable videolaryngoscope [29] invented in 2010, equipped with several blades for different age groups. Its specific feature is the angulated blade [29]. The technique for introducing UEScope does not demand tongue sweep.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] These facts have greatly facilitated the progress of clinical airway management and resulted in the development of new related strategies and techniques. [ 5 ] Furthermore, in numerous nations, practice guidelines have been developed to assist anesthesiologists for safe airway management in perioperative period. [ 6 7 8 9 10 11 12 ] Due to those tremendous efforts, the incidence of serious complications related to airway management has been significantly decreased.…”
mentioning
confidence: 99%